2013
DOI: 10.1523/jneurosci.0830-13.2013
|View full text |Cite|
|
Sign up to set email alerts
|

Coordinated Regulation of Hepatic Energy Stores by Leptin and Hypothalamic Agouti-Related Protein

Abstract: Like obesity, prolonged food deprivation induces severe hepatic steatosis; however, the functional significance of this phenomenon is not well understood. In this study, we show that the fall in plasma leptin concentration during fasting is required for the development of hepatic steatosis in mice. Removal of leptin receptors from AGRP neurons diminishes fasting-induced hepatic steatosis. Furthermore, the suppressive effects of leptin on fasting-induced hepatic steatosis are absent in mice lacking the gene enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…In mice, deficient leptin signaling in the hypothalamus blunts the fasting lead suppression of hepatic sympathetic activity and elevation of hepatic triglyceride content and steatosis [10]. Furthermore, severe hepatic steatosis seen in congenital lipodystrophies can be treated with metreleptin [11,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, deficient leptin signaling in the hypothalamus blunts the fasting lead suppression of hepatic sympathetic activity and elevation of hepatic triglyceride content and steatosis [10]. Furthermore, severe hepatic steatosis seen in congenital lipodystrophies can be treated with metreleptin [11,24].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, fasting leads to suppression of hepatic sympathetic activity and elevated hepatic triglyceride content and steatosis. These effects are blunted in mice with deficient leptin signaling in the AGRP neurons in the hypothalamus [10]. In humans, congenital leptin deficiency is associated with severe hepatic steatosis, which can be treated with metreleptin [11].…”
Section: Introductionmentioning
confidence: 99%
“…These effects were dependent on hypothalamic leptin signaling and were, surprisingly, caused by a stimulation of SNS outfl ow to the liver, as evidenced by an increase in hepatic noradrenalin content ( 41 ). In addition, a recent follow-up study showed that leptin administration in 36 h-fasted mice decreased hepatic TG content, lipogenic gene expression, and VLDL-TG production ( 42 ). These data, however, should be taken with caution, as 36 h fasting is probably a nonphysiological metabolic condition for mice.…”
Section: Anatomy Of Hypothalamic Sympathetic Outflowmentioning
confidence: 99%
“…The central nervous system, and more specifically, the hypothalamus has a major regulatory role in peripheral tissue functions in health and disease (Dietrich et al, 2012; Matarese et al, 2013; Ruan et al, 2014; Warne et al, 2013). A growing body of evidence indicates that the hypothalamus also affects bone homeostasis mediated, at least in part, by the autonomic nervous system and endocrine organs (Ohlsson et al, 2012; Sato et al, 2007; Yadav et al, 2009).…”
Section: Introductionmentioning
confidence: 99%